Pharmacologic inhibition of dipeptidyl peptidase 1 (cathepsin C) does not block in vitro granzyme-mediated target cell killing by CD8 T or NK cells - Sutton, Vivien R.; Watt, Sally V.; Akhlaghi, Hedieh; Cipolla, David C.; Chen, Kuan-Ju; LaSala, Daniel; McDonald, Patrick P.; Beavis, Paul A.; Munoz, Isabelle; Hodel, Adrian W.; Noori, Tahereh; Voskoboinik, Ilia; et al. (Frontiers in Pharmacology, 2024)
Recently developed small molecule inhibitors of the lysosomal protease dipeptidyl peptidase 1 (DPP1), also known as cathepsin C (CatC), can suppress suppurative inflammation in vivo by blocking the processing of zymogenic (pro-) forms of the neutrophil serine proteases (NSPs), including neutrophil elastase, proteinase 3, and cathepsin G. However, DPP1 also plays an important role in activating granzyme serine proteases expressed by cytotoxic T lymphocytes (CTL) and natural killer (NK) cells. Therefore, it is critical to determine whether inhibition of DPP1 can also cause 'offtarget' suppression of CTL/NK cell mediated killing of virus-infected or malignant cells. Here, we demonstrated that the processing of human granzymes A and B, transitioning from a zymogen to an active protease, is not solely dependent on DPP1. As a result, the killing of target cells by primary human CD8+ T cells, NK cells, and gene-engineered anti-CD19 CAR T cells was not blocked in vitro, even after prior exposure to high concentrations of the reversible DPP1 inhibitor, brensocatib.Consistent with this, the turnover of model granzyme A/B peptide substrates in human CTL/NK cell lysates was not significantly reduced by brensocatib. In contrast, pre-incubation with brensocatib almost entirely abolished (>90%) both the cytotoxic activity of mouse CD8+ T cells against cognate target cells and granzyme substate turnover. Overall, our finding that the effects of DPP1 inhibition on human cytotoxic lymphocytes are attenuated in comparison to the mouse indicate that granzyme processing/activation pathways differ between mice and humans. Moreover, our in vitro data suggest that human subjects treated with reversible DPP1 inhibitors, such as brensocatib, are will be unlikely to experience any appreciable deficit in CTL/NK cell-mediated immunity.